How is circadian preference associated with cyber-victimization? A moderated mediation model of hostile recognition and online self-disclosure in Chinese early adolescent students - Jia, Yanru; Wu, Yuntena; Jin, Tonglin; Zhang, Lu (Frontiers in Psychology, 2022)
Although circadian preference is widely accepted to be a risk factor in the increase of adolescents’ negative experiences, little is known about its association with cyber-victimization. The current study sought to examine whether eveningness was significantly related to adolescents’ negative experiences. We further examined in-victimization events and whether hostile recognition and online self-disclosure played a vital role in eveningness and adolescents’ cyber-victimization. Study participants included 583 adolescents from four middle schools in China who completed questionnaires regarding their circadian preference, hostile recognition, online self-disclosure, and experience with cyber-victimization. Results indicated that adolescents with a high level of eveningness were more likely to experience cyber-victimization. Hostile recognition significantly mediated the relationship between eveningness and adolescents’ cyber-victimization. Furthermore, online self-disclosure moderated the indirect relationship between eveningness and cyber-victimization. Specifically, the paths from eveningness to hostile recognition and from hostile recognition to cyber-victimization became strengthened when adolescents experienced high levels of online self-disclosure. The results imply that researchers should pay more attention to remote factors, such as adolescents’ circadian preference and their relationship with cyber-victimization, to help them adapt to school requirements and reduce the frequency of victimization.